THE ROLE OF HORMONES OF HAPPINESS AND JOY IN HUMAN LIFE - S, Movlonova (Журнал естественных наук, 2023)
Hormones are biologically active substances that the body produces under the influence of various external and internal factors. Thanks to them, a person is able to experience happiness, bliss and love.